Complex Interactions Between Human Immunodeficiency Virus Type-1, Sex, and Osteopontin Influence Viral Replication and Leukocyte Proportions in Tissues - Mahmud, Farina J.; Greif, Elizabeth; Boucher, Thomas; Metcalf Pate, Kelly A.; Lyons, Claire; Carlson, Bess; Brown, Amanda M. (Frontiers in Virology, 2021)
Evidence suggesting that HIV pathogenesis differs by sex, a variable known to influence the extent and breadth of immune responses in health and disease continues to accumulate. Host factors that promote or inhibit HIV replication may do so in a way that varies by sex. Prior studies using cultured human macrophages demonstrated that osteopontin (OPN)/secreted phosphoprotein-1 (SPP1) stimulates HIV replication. To test whether OPN has the same positive impact on virus replication at the level of tissues, we used a humanized mice model of low-level chronic HIV infection and in which OPN RNA and protein expression was inhibited with targeted aptamers. Interestingly, 4 months after infection when there were no significant differences in HIV viral load in plasma between groups however in contrast, in the spleen, lung, and liver the tissue burden of HIV RNA, as well as the proportion of leukocytes in female and male mice differed depending on whether OPN was expressed or not. The findings collectively demonstrate the potential for complex interactions between host factors like OPN and sex to influence different facets of HIV tissue-level pathogenesis.